Precedents as a Source of Land Law in Poland’s Past - Lesiński, Bogdan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Prejudykaty jako źródło prawa ziemskiego w dawnej Polsce by Bogdan Lesiński published originally in “Czasopismo Prawno-Historyczne” from 1990. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.